Peta Pengetahuan Penelitian Deforestasi dan Bencana di Indonesia: Analisis Bibliometrik dan Implikasi Transformasi Digital - Mahmud, Muslimin; Supriyadi, Asep Adang (UNIB Press, 2026)
Indonesia's forests play a strategic role in maintaining ecosystem balance, but increasing deforestation and land degradation have increased the risk of environmental disasters, particularly flooding in Sumatra. As scientific attention has increased, research on Indonesian forests has grown rapidly but remains multidisciplinary and fragmented. This study aims to map the knowledge structure, thematic dynamics, and patterns of global collaboration in deforestation and disaster research in Indonesia, and to examine the integration of digital transformation into these studies. This study uses a descriptive quantitative approach through bibliometric analysis of 175 Scopus-indexed journal articles extracted using the keyword